2022
DOI: 10.3390/s22103929
|View full text |Cite
|
Sign up to set email alerts
|

Research on Theory and a Performance Analysis of an Innovative Rehabilitation Robot

Abstract: This paper presents an innovative application of a 6-DOF robot in the field of rehabilitation training. This robot operates in a parallel fashion for lower limb movement, which adopts a new structure that can help patients to carry out a variety of rehabilitation exercises. Traditional parallel robots, such as the Stewart robot, have the characteristics of strong bearing capacity. However, it is difficult to achieve high-speed, high-acceleration and long journey movement. This paper presents a new robot config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Based on the above bibliometric results, combined with the authors’ understanding, we identified research hotspots for AI research in spinal cord neural injury and restoration: Intelligent robots and limb exoskeletons for assisted rehabilitation: there is no doubt that these physical branches of AI are the most significant research hotspot of AI in the field of spinal cord neural injury and restoration, which is multiply verified from the keyword analysis, literature co-citation analysis, and the hotspot analysis of highly co-cited literature. Rehabilitation robots are interactive motorized devices that allow fine limb movement and precise measurements ( 27 ). They are typically divided into exoskeletons that assist in limb movement by controlling the displacement of each segment and end-effector devices capable of mobilizing the limb from a distal point of application.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above bibliometric results, combined with the authors’ understanding, we identified research hotspots for AI research in spinal cord neural injury and restoration: Intelligent robots and limb exoskeletons for assisted rehabilitation: there is no doubt that these physical branches of AI are the most significant research hotspot of AI in the field of spinal cord neural injury and restoration, which is multiply verified from the keyword analysis, literature co-citation analysis, and the hotspot analysis of highly co-cited literature. Rehabilitation robots are interactive motorized devices that allow fine limb movement and precise measurements ( 27 ). They are typically divided into exoskeletons that assist in limb movement by controlling the displacement of each segment and end-effector devices capable of mobilizing the limb from a distal point of application.…”
Section: Discussionmentioning
confidence: 99%
“…The main function of the robot is to help patients train by simulating normal activities. It can also be worn on the patient to force them to perform various rehabilitation exercises, continuously stimulating their brains, improving the ability of their motor organs, and achieving an early recovery [ 97 ]. Robot-assisted rehabilitation systems mostly monitor hand extension, flexion, and wrist movements in the field of stroke rehabilitation, and there are few studies on fine movements, such as finger coordination activities.…”
Section: Discussionmentioning
confidence: 99%
“…One-dimensional sliding in the horizontal direction is achieved through these linear pairs. The motion and power of these linear pairs are transmitted to the vestibular end platform through the connecting rods and the spherical wrists [14]. The end platform has 6 DOFs, and the mechanical interface on this platform is the installation benchmark of the proprioception platform.…”
Section: A Robot Structurementioning
confidence: 99%